Sintesis Heptapeptida Linear (H-Tyr-Asp-Pro-Ala-Pro-Pro-Pro-Oh) dengan Menggunakan Dic/Oksima sebagai Reagen Pengkopling - Rani Maharani; Eka Fitri Yanti (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2016)
A tetrapeptide, an analog of trypsin-modulating oostatic factor (TMOF), has been synthesised by using a method of solid-phase peptide synthesis on 2-chlorotrityl chloride resin. Fmoc strategy was applied on the synthesis. The formation of peptide bond was facilitated by DIC/oxime as coupling reagent. After all of amino acids were attached on the resin, tetrapeptidyl resin was added by a mixture of TFA:water:EDT(90:5:5) in dichloromethane to cleave the peptide.Crude peptide was purified by reverse-phase column chromatography and the purified peptide was analysed by TOF ES-MS spectroscopy.